Preparation of biosorbent from avocado seeds for preconcentration and simultaneous extraction of trace parabens in environmental wastewater samples - Nephiphidi, Aluwani Sharon; Mudzielwana, Rabelani; Selahle, Shirley Kholofelo (Frontiers in Chemistry, 2025)
The identification of emerging contaminants, including parabens, in water resources and aquatic ecosystems has become an issue of environmental concern due to the associated human and ecological risks, emphasizing the urgent need for effective monitoring and remediation strategies. This study aimed to synthesize a low-cost magnetic activated carbon biosorbent from avocado seeds, achieving higher extraction efficiencies and paving the way for more sustainable water treatment methods. The Dispersive Magnetic Solid-Phase Microextraction (DMSPME) technique was used for the preconcentration and simultaneous extraction of parabens (methylParaben, ethylParaben, and butylParaben). Influential DMSPME parameters were optimized using a Fractional factorial design for screening and a central composite design for further analysis. Characterization results have proved that the desired biosorbent was successfully synthesized. The magnetic activated carbon showed a well-defined surface with exhaustive characterization of Brunauer-Emmett-Teller (BET) revealed surface areas of 30 m2/g and a pore volume of 0.1 cm3/g. The exhaustive characterization of the Scanning Electron Microscope (SEM) image revealed that the incorporation of iron oxide into the activated carbon resulted in the formation of small, well-defined pores. The Energy Dispersive X-Ray (EDS) indicated the existence of carbon, oxygen, iron, sodium, and potassium. The Fourier-Transform Infrared Spectroscopy (FTIR) analysis revealed the presence of several functional groups, including carboxylic acid, iron oxide, and aromatic compounds. This characterization confirmed that Magnetic activated carbon prepared with 30% KOH was the best biosorbent in extracting the targeted parabens. The parameters of interest were biosorbent amount, sample volume, type of elution solvent, pH, and volume of extraction solvent. The optimum parameters obtained were 22.5 mg of 30% KOH-magnetic carbon activated, 6.5 pH, and 875 µL methanol as elution solvent. These conditions lead to obtaining good relative recoveries of 80.0%–101%. Limit of detection (LOD) and Limit of quantification (LOQ) of the method were 0.12–0.19 μg/L and 0.25–0.49 μg/L, respectively. The reusability and regeneration adsorption percentage recoveries significantly decreased after the fifth cycle. Parabens extraction using the 30% KOH- magnetic activated carbon was considered a capable biosorbent for the extraction of parabens because it demonstrated a strong potential for extracting parabens pollutants simultaneously in wastewater samples.